Examining the impact of greenwashing on customer boycott intentions: the mediating role of green confusion - Ngan Bich Nguyen; Tung Duy Duong (Discover Sustainability)
Abstract This study investigates how greenwashing—a practice where companies falsely promote their products or actions as environmentally friendly—influences customers' intentions to boycott a business, specifically by examining the role of customer confusion (green confusion). Using the "Green Arm" campaign by Highlands Coffee in Vietnam as an example, the research explores how misleading environmental claims affect consumer behavior. The main goal is to understand how greenwashing impacts customer boycotts by creating confusion. The study uses a well-established theory called Stimulus-Organism-Response (S–O-R) to structure the research, applying a quantitative approach to test the relationships among greenwashing, green confusion, and customer boycott intentions. Results show a clear link that when businesses make deceptive environmental claims, customers become confused and uncertain. This confusion then increases the likelihood of customers choosing to boycott the business. This research contributes to the understanding of consumer reactions to dishonest green marketing practices and offers practical guidance for companies seeking to avoid negative customer responses by being honest and clear in their sustainability efforts. The findings are valuable for both business managers and regulatory bodies looking to better understand and manage customer perceptions regarding corporate environmental responsibility.